Pengaruh Marketing Mix Terhadap Keputusan Pembeli Motor Yamaha Pada PT. Hasjrat Abadi Manado - Tjahyadi, Zifora Rilifta; Sumayku, Sontje; Tumbel, Tinneke M (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
The purpose of this research is to find out the influence of marketing mix to the decisionof buyer of Yamaha motor at PT. Hasjrat Abadi Manado. The influence of the rapiddevelopment of the era makes every company should always do research anddevelopment to always be on a comfortable track. Seeing this, companies need to createbreakthroughs and strategic innovations in order to continue to increase revenue andprofits both quantitatively and qualitatively. PT. Hasjrat Abadi is the exclusivedistributor of Toyota and Yamaha vehicles in eleven leading provinces, parts of centraland eastern Indonesia. Tight competition is mainly happening on Yamaha and Hondafor the top spot. Yamaha motorcycle sales growth in December increased compared toHonda. Therefore, researchers who are interested in taking the title of the research are:"The influence of marketing mix to the decision of Yamaha motorcycle buyer in PTHasjrat Abadi Marketing mix is a combination of four variables or activity which is thecore of marketing company System: product, price, And distribution system (Assauri,2011.) According to Schifman and Kanuk (2007) the decision is the selection of two ormore alternative options In other words, alternative choice must be available to aperson When making a decision Based on the results of research on the product testobtained value (0.00) , The price has value (0,048), whereas place value (0,023) andpromotion is (0,001), the bias is said that all the variables are significant The discussioncan be summarized as follows: Products are partially positive and significantlyinfluence the decision of buyer motor Yamaha in PT Hasjrat Abadi Manado, theproduct is variable te Which affect buyer decisions. Partially positive and significantinfluence decision of Yamaha motorcycle buyer in PT Hasjrat Abadi Manado. Price isthe fourth highest variable. Variables that affect buyer decisions. Place was partiallypositive and significant effect on the decision of Yamaha motorcycle buyers in PT.Hasjrat Abadi Manado. Place is the third highest variable affecting buyer decisions.Promotion partially have a positive and significant effect on purchasing decision ofYamaha motor at PT. Hasjrat Abadi Manado. Promotion is the second highest variablethat influences buyer decisions. Simultaneously product, price, place and promotionhave an effect on signifikan to decision of buyer of Yamaha motor at PT. Hasjrat AbadiManado.Keywords: Marketing Mix, Buyer Decision